Hubungan Asupan Energi Dan Aktivitas Fisik Dengan Status Gizi Atlet Taekwondo Koguryo Manahan Surakarta - Zildanti, Cut (2016)
Constraints in dealing with managing energy intake a lot of taekwondo athletes do not understand and realize the importance of eating nutritious foods to help increasing performance. Physical activity done by adolescent athletes is higher than adolescents who are not athletes. This research aimed to find the correlation between energy intake and physical activity and nutritional status of Koguryo Taekwondo Athlete Manahan Surakarta. This research was an observational study with cross-sectional design. The subjects were 34 adolescents aged 12-15 years old. Data collection included the identity of respondents, were obtained from the questionnaires, the energy intake data were obtained from food recall 24 hours for 4 unconsecutive days, physical activity data were obtained through 24-hour recall physical activity for 7 days. The analysis tests used the Pearson Product Moment Tests. All subjects had low energy intake, 85.3% of the subjects had a moderate of physical activity levels, 64.7% of the subjects had normal nutritional status, most of the subjects were 13 years old (41.2%). There was no correlation between energy intake and nutritional status, with p=0.060. There was no correlation between physical activity and nutritional status with a value of p=0.094.